MOTIVASI TERHADAP PELAYANAN YANG BERKUALITAS - Nazwirman Nazwirman (Cakrawala - Jurnal Humaniora, 2009)
To motivate employees is very needed and to give satisfaction to all of customers or client depend on human resources, ability, capable and skill in the quality service to get reach organization or company goal. Positive attitude and behavior somebody is one of the factor as supporter. Laeader ship style company must be able to manage and development quality service culture all of performance individual of each in the organization or company to reach competitive advance and should have customer satisfaction good intern and extern.Keywords: Motivation, Quality Service